THE LI NIHA MAINTENANCE AMONG NIAS TEENAGERS OF ORAHUA MAHASISWA NIAS (OMN) MEDAN IN KELURAHAN LAUCI MEDAN TUNTUNGAN - Riswan Zega; Busmin Gurning; Lince Sihombing (LINGUISTIK TERAPAN, 2018)
This study explained the Li Niha Maintenance among Teenagers of OrahuaMahasiswaNias (OMN) Medan in Kelurahan Lauci Medan Tuntungan. The objectives were (1) to investigate what maintenance of Li Niha is preserved by the Nias teenagers of OMN Medan (2)to describe how is the Li Niha maintained by the Nias teenagers of OMN Medan (3) to explain the reason why is the Li Niha maintained by the Nias teenagers of OMN Medan. This study applied phenomenological design as a part of qualitative research design. Data were words or utterances of 20 persons teenager of OMN Medan collected through observation and interview techniques. The data were analyzed by using Bogdan & Biklen, (1992). The findings of this study showed that: (1) four types of Li Niha maintenance preserved by the teenagers of OMN Medan namely strong, dominant, moderate and weak maintenance; (2) four ways of Li Niha maintained by Nias teenagers of OMNMedan,; and (3) five reasons the teenagers of Orahua Mahasiswa Nias (OMN) Medan  in Kelurahan Lauci Medan Tuntungan maintain Li Niha. Keywords: Language Shift, Maintenance, Intermarriage, Qualitative